Policy And Criminal Law Enforcement Against The Perpetrators S Of Corruption: “Reorientation Objective Of Condemnation” - Hambali Yusuf (International Journal Reglement & Society (IJRS), 2021)
This article is a reorientation of the objectives of corruption condemnation.The problem that arises is the imprisonment election policy as the primary penalty which is not in line with the philosophy of criminal law objectives in the economic field.The criminal formulation policy is the most strategically determining the law enforcement policy by judge. The policy on the formulation of imprisonment in Corruption Law Act is at the most , both formulated in cumulative fines or mulative alternative fines penalties. The imprisonment have many weakness, some criticism comes from academic and international institutions.The effectiveness of imprisonment and fines is highly questionable. The objective of EAS needs to be reoriented, which is from the condemnation retaliation objective of imprisonment to the returning the State losses by fines penalty, namely by optimizing fines penalty.In addition there are two fundamental reasons, first, the philosophical issue, that the objective of the imprisonment should provide a justice sense for all the parties, which in turn away from justice sense. econdly, a theoretical problem is found, where the theories of imprisonment cannot explain the benefits of imprisonment both for the convicted, for the victim, and for the society. There are two conclusions, that the imprisonment policy is not effective in achieving the objective of corruption condemnation to protect the State's financial losses from corruption .The sentencing of both imprisonment and fines for the perpetrators are still very low and do not represent criminal sanctions as an extraordinary crimes.